Can algae-based technologies be an affordable green process for biofuel production and wastewater remediation?. (May 2018) - Vo Hoang Nhat, P.; Ngo, H.H.; Guo, W.S.; Chang, S.W.; Nguyen, D.D.; Nguyen, P.D.; Bui, X.T.; Zhang, X.B.; Guo, J.B.
Graphical abstract: Highlights: Microalgae has more lipid content while macroalgae is rich of carbohydrate. Algae is efficient in nutrients removal. Combined processes, optimization and algae strains screening are important. Revenues in algae-based biofuel production and wastewater remediation are limited. Policy and social support for commercialization are lacking. Abstract: Algae is a well-known organism that its characteristic is prominent for biofuel production and wastewater remediation. This critical review aims to present the applicability of algae with in-depth discussion regarding three key aspects: (i) characterization of algae for its applications; (ii) the technical approaches and their strengths and drawbacks; and (iii) future perspectives of algae-based technologies. The process optimization and combinations with other chemical and biological processes have generated efficiency, in which bio-oil yield is up to 41.1%. Through life cycle assessment, algae bio-energy achieves high energy return than fossil fuel. Thus, the algae-based technologies can reasonably be considered as green approaches. Although selling price of algae bio-oil is still high (about 2 L −1 ) compared to fossil fuel's price of 1 L −1, it is expected that the algae bio-oil's price will become acceptable in the next coming decades and potentially dominate 75% of the market.